2017
DOI: 10.1515/rpp-2017-0061
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Developing Professional Mobility of Teachers in the Works of Foreign Scholars

Abstract: The article analyzes the positions of foreign and domestic scholars on the problem of developing professional mobility of teachers. It has been stated that today professional mobility is a necessary component of training a skilled worker. It has been indicated that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…According to the author, "the choreographic educational process is distinguished from the pedagogical system, the basis, first of all, by the artistic direction in the development of creative abilities of students, including dance imagination. The dance expresses the State, feelings, moods, feelings of the performer and performs the corresponding content" (Pavlenko, 2017) Most studies have identified the most important tasks for improving the effectiveness of joint pedagogical activities of teachers-choreographers and ballet concertmasters. According to the author, "in the process of work of teachers of special choreographic disciplines and concertmasters as fullfledged participants in the pedagogical process, the tasks are to reveal the personality of students, develop their abilities, especially musicality, dance skills, and the ability to see their future profession aesthetically" (Khalid, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the author, "the choreographic educational process is distinguished from the pedagogical system, the basis, first of all, by the artistic direction in the development of creative abilities of students, including dance imagination. The dance expresses the State, feelings, moods, feelings of the performer and performs the corresponding content" (Pavlenko, 2017) Most studies have identified the most important tasks for improving the effectiveness of joint pedagogical activities of teachers-choreographers and ballet concertmasters. According to the author, "in the process of work of teachers of special choreographic disciplines and concertmasters as fullfledged participants in the pedagogical process, the tasks are to reveal the personality of students, develop their abilities, especially musicality, dance skills, and the ability to see their future profession aesthetically" (Khalid, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Domestic mobility studies are characterised with a fairly clear separation of socio-economic, psychological and pedagogical approaches. They are aimed at forming mobility of specialists of different spheres with the focus on their personal (Sergeeva, 2015), psychological (Kerdyasheva, 2010) and motivational (Nedelʹko, 2007) readiness for professional mobility; comparing the international practice of investigating the issue (Sergeeva, 2015;Pavlenko, 2017;Semenog, 2016). Perhaps, the convergence and interpenetration of these currently uncorrelated approaches is a promising direction for domestic mobility studies.…”
Section: Introductionmentioning
confidence: 99%